Behavioral health promotion interventions to increase cervical cancer screening uptake: A systematic review - Mei Rosyidah; Elviera Gamelia; Suratman Suratman (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Cervical cancer is the fourth most common cancer in women worldwide, disproportionately affecting those in low- and middle-income countries (LMICs). Despite the availability of effective screening tools such as Pap test and HPV testing, participation rates remain suboptimal due to complex behavioral barriers including low awareness, cultural stigma, and limited access to healthcare services. Purpose: To synthesize evidence on behavioral-based health promotion interventions designed to increase cervical cancer screening uptake, examining their theoretical frameworks, delivery modalities, and effectiveness. Method: A systematic search was conducted in three electronic databases—PubMed/MEDLINE, Scopus, and ScienceDirect—for studies published between January 2015 and March 2026. The PRISMA 2020 framework guided the review process. Studies evaluating behavioral interventions targeting cervical cancer screening in women eligible for or targeted by cervical screening were included. Results: A total of 760 records were identified from three databases (PubMed: n=32; Scopus: n=463; ScienceDirect: n=265). After removing 38 duplicates, 722 records were screened; 159 proceeded to full-text assessment, and 54 studies from 25 countries were ultimately included. Interventions were categorized as: face-to-face health education (n=18), digital/mHealth (n=11), reminder-based systems (n=7), motivational interviewing (n=4), peer-led education (n=4), culturally tailored programs (n=7), and multicomponent strategies (n=3). Theoretical frameworks used included the Health Belief Model, Protection Motivation Theory, and Social Cognitive Theory. Of 54 studies, 47 (87.0%) reported statistically significant improvement in at least one outcome in screening uptake or related behavioral outcomes. Conclusion: Behavioral-based health promotion interventions effectively increase cervical cancer screening uptake. Theory-driven, culturally tailored, and multicomponent approaches demonstrate the most consistently favorable findings and should be prioritized in public health programs.